Vibration Modes of the Cello Tailpiece - FOUILHE, Eric; GOLI, Giacomo; HOUSSAY, Anne; STOPPANI, George (Archives of Acoustics, 2013)
The application of modern scientific methods and measuring techniques can ex-tend the empirical knowledge used for centuries by violinmakers for making andadjusting the sound of violins, violas, and cellos.Accessories such as strings and tailpieces have been studied recently with respectto style and historical coherence, after having been somehow neglected by researchersin the past. These fittings have played an important part in the history of theseinstruments, but have largely disappeared as they have been modernised. However,the mechanics of these accessories contribute significantly to sound production inways that have changed over time with different musical aesthetics and in differenttechnical contexts. There is a need to further elucidate the function and musicalcontribution of strings and tailpieces.With this research we are trying to understand the modifications of the cello’ssound as a consequence of tailpiece characteristics (shape of the tailpiece and typesof attachments). Modal analysis was used to first investigate the vibration modes ofthe tailpiece when mounted on a non-reactive rig and then when mounted on a realcello where it can interact with the modes of the instrument’s corpus. A preliminarystudy of the effect of the tailpiece cord length will be presented.